2020
DOI: 10.21203/rs.2.23247/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control Group Design in a Complex Intervention Study: Challenges, Dilemmas and Possible Solutions

Abstract: Background The use of a control group is one of the most critical components of an RCT. The control conditions may change over time and include assessment interviews and standard stroke treatment. Therefore, the control group should be monitored and described in as much detail as the intervention group. It is important to find ways to reduce the risk of study-induced influence on the members of the control group. The aim of this study was to explore the possible influence of the assessment interviews on the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…While participants in the present study initially expressed overall negative feelings and disappointment about being waitlisted, there were some participants who felt that knowing help would be coming made the six-week wait time more manageable. These results are in keeping with findings from previous non-perinatal mental health and surgical waitlist studies (8)(9)(10). Participants in the present study identified coping strategies that they found helpful during the waitlist period, many of which have been reported across the waitlist literature, in particular, peer support, self-help materials, and other professional supports (7,10).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…While participants in the present study initially expressed overall negative feelings and disappointment about being waitlisted, there were some participants who felt that knowing help would be coming made the six-week wait time more manageable. These results are in keeping with findings from previous non-perinatal mental health and surgical waitlist studies (8)(9)(10). Participants in the present study identified coping strategies that they found helpful during the waitlist period, many of which have been reported across the waitlist literature, in particular, peer support, self-help materials, and other professional supports (7,10).…”
Section: Discussionsupporting
confidence: 91%
“…In keeping with previous research that sought to explore the waitlist experiences of patient populations awaiting medical procedures or mental health services (e.g., surgery, mental health support) (1,(4)(5)(6)(7)(8)(9)(10)48), a qualitative design was used to describe the waitlist experiences of expectant and new mothers experiencing anxiety during the perinatal period. To understand the nuance and complexities of participants' experiences, we followed Braun and Clarke's (49,50) reflexive thematic analysis approach along with Tracy's (51) criteria for qualitative rigor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations